Effects of verbal coach encouragement during large-sided games on selected physical, psychological and technical performance variables in women’s soccer - Ridwan, Mochamad; Hartoto, Setiyo; Kartiko, Dwi Cahyo; Ningsih, Yuni Fitriyah; Kurtoğlu, Ahmet; Widiyanto, Wahyu Eko; Hamidi, Ahmad; Lobo, Joseph; Bahriyanto, Ahmad; Sanjaykumar, Swamynathan; Muracki, Jarosław; Setiawan, Edi (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. The study aimed to reveal the effects of verbal encouragement during large-sided games on physical, psychological, and technical performance among female soccer players.Methods. Thirty-two female soccer players participated and were assigned to verbal encouragement and large-sided games (n = 16) and control groups (non-verbal encouragement, n = 16). Tests included the 20 m sprint test, Illinois Agility Test (IAT), multistage fitness test (MFT), Physical Activity Enjoyment Scale (PACES), Satisfaction Scale for Athlete (SSA), and the assessment of technical execution skills. Results. Group effects were detected on physical performance variables (all p < 0.001), while there were interaction effects on some physical performance components (p < 0.001), but not in the 20 m sprint test (p = 0.144). There were effects of time and interactions on psychological variables (all p < 0.001), with group effects on some psychological components (p < 0.001), except for PACES positive feelings (p = 0.692). Furthermore, a time effect was found on the technical variables (all p < 0.001), with a group effect on some technical components (p < 0.001), excluding successful tackles (p = 0.432). There was also an interaction on some technical components (p < 0.001), but no affect on failed to shoot (p = 0.439).Conclusions. The study highlights the importance of using verbal encouragement in large-sided games to improve physical, psychological, and technical performance among female soccer players.
Keywords: women’s soccer; game exercise; competitive performance; verbal encouragement